STUDY ON BACTERIOLOGICAL QUALITY OF WATER USED FOR DRINKING PURPOSE FROM WESTERN REGION OF UTTAR PRADESH - BHATT, HITESH; Kiran, Enugala Ravi; Madasu, Kumar Raja (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to the bacteriological nature of drinking water from different dynamic sources of water used in the catchment region of a tertiary care teaching hospital. Methods: Fifty water tests were performed for the review. Standard guidelines for drinking water quality appraisal were embraced. Culture and bacteriological trial of drinking water were preceded according to standard conventions. After assemblage of gathered information, examination was performed by statistical software. Results: Out of 50 water tests gathered, 24 were viewed as inadmissible. Escherichia coli was viewed as liable for about a fourth of tests, while Pseudomonas in 1/5th of gathered examples. E. coli and Klebsiella tried positive with Methyl Red while Pseudomonas spp. what’s more, Klebsiella tried positive with Citrate test reagent. E. coli showed positive outcome with Indole reagent though Klebsiella tried positive with Urease. With respect to populace life forms, E. coli, Klebsiella Spp., and Pseudomonas Spp. were viewed as certain in one sample though Klebsiella Spp. furthermore, Pseudomonas Spp. was viewed as certain another one sample. Conclusion: The review featured unsafe nature of water sources in the study region with respect to drinking water which is not good for utilization of water. Reconnaissance of water sources and normal bacteriological evaluation of all water hotspots for drinking is suggested on regular basis.